2011
DOI: 10.1093/anatox/35.2.119
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Acute Hydrogen Sulfide Poisoning Caused by Hydrogen Sulfide: Hydroxocobalamin Therapy for Acute Hydrogen Sulfide Poisoning

Abstract: A patient committed suicide with hydrogen sulfide (H(2)S) by combining two commercial products. The patient was given hydroxocobalamin as an antidote in addition to treatment with cardiopulmonary resuscitation, but died approximately 42 min after his arrival at the hospital. The patient's cause of death was attributed to acute hydrogen sulfide poisoning. Serum concentrations of sulfide before and after administration of hydroxocobalamin were 0.22 and 0.11 μg/mL, respectively; serum concentrations of thiosulfat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…Anecdotal reports have mentioned the prompt use of hyperbaric oxygen therapy or hydroxocobalamin but these options remain controversial [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal reports have mentioned the prompt use of hyperbaric oxygen therapy or hydroxocobalamin but these options remain controversial [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…These trends are congruent with our experiments examining the efficacy of cobinamide to treat cyanide toxicity. 9 Although hydroxocobalamin has been shown to bind sulfide and thiosulfate, 22 it was not clinically effective in this model at the same mg/kg dose as cobinamide. This result is consistent with our previous work with cyanide where the effective hydroxocobalamin dose was about 5…”
Section: Accepted Articlementioning
confidence: 88%
“…22 Our intent in this experiment was to demonstrate that cobinamide is more efficacious compared to hydroxocobalamin on a mg/mg basis. We have previously shown that hydroxocobalamin is as effective as cobinamide in reversing cyanide toxicity but five times more hydroxocobalamin than cobinamide was required.…”
Section: Accepted Articlementioning
confidence: 99%
“…70 The cyanide antidote hydroxocobalamin has also been used. 71,72 Some authors have proposed hyperbaric oxygen. 73 Anhydrous Ammonia (NH 3 ).…”
Section: Pathophysiology and Clinical Carementioning
confidence: 99%